Uptown - Collier, Bryan (New York : Henry Holt, 2000)
A tour of the sights of Harlem, including the Metro-North Train, brownstones, shopping on 125th Street, a barber shop, summer basketball, the Boy's Choir, and sunset over the Harlem River.
Keywords: African Americans -- Fiction; Harlem (New York, N.Y.) -- Fiction